Identification and Treatment of Opioid Withdrawal and Opioid Use Disorder in the Emergency Department - Lindsey Jennings; Tessa Warner; Bastien Bacro-Duverger (Association of American Medical Colleges, 2020)
Introduction Opioid addiction and misuse constitute a public health crisis in the United States. Recent research supports buprenorphine induction in the emergency department (ED) setting for patients with opioid use disorder (OUD). However, education regarding buprenorphine induction for emergency medicine (EM) physicians, residents, and students is still limited. Methods We created a 1-hour introductory workshop for the identification and treatment of opioid withdrawal and OUD in the ED for medical students going into EM and for EM interns. The workshop consisted to two distinct curricular sections: (1) a didactic session providing an overview of the basic knowledge and skills to identify and treat patients with OUD in the ED and (2) a case-based session in which students worked through the identification of opioid withdrawal; discussion of opioid use with the patient, going through the steps of SBIRT (screening, brief intervention, and referral to treatment); and considerations when starting buprenorphine. The workshop was evaluated using a pre- and posttest examining medical knowledge around buprenorphine use in the ED. Results A total of 48 students and interns participated in the curriculum. The students showed a significant improvement in medical knowledge between the pre- and posttests, with an average 45% higher score on the posttest (p < .001). Discussion Our workshop resulted in a short-term improvement in medical students' and interns' knowledge of the identification and treatment of patients with OUD in the ED.